2017
DOI: 10.1016/j.carj.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Peer Review in Radiology: How Can We Learn from Our Mistakes?

Abstract: I would give great praise to the physician whose mistakes are small, for perfect accuracy is seldom to be seen.-Hippocrates [1]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Analyses of opinions regarding reviewer feedback on submission of articles indicated that, while most users agreed reviewer feedback was of good quality, there were widely varying opinions for each of the quality categories. These findings were consistent with multiple previous publications describing challenges inherent in both giving and receiving reviewer feedback . The general consensus from these publications was that the peer review process is imperfect and that neither the giver nor receiver enjoy the process.…”
Section: Discussionsupporting
confidence: 90%
“…Analyses of opinions regarding reviewer feedback on submission of articles indicated that, while most users agreed reviewer feedback was of good quality, there were widely varying opinions for each of the quality categories. These findings were consistent with multiple previous publications describing challenges inherent in both giving and receiving reviewer feedback . The general consensus from these publications was that the peer review process is imperfect and that neither the giver nor receiver enjoy the process.…”
Section: Discussionsupporting
confidence: 90%
“…Recently published papers on the peer review experience identify important opportunities to create a non-punitive peer review system, truly focused on learning from the errors we all make [ 9 ]. It was mentioned that radiologists’ reporting performance cannot be perfect and some errors are inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…Error-reduction strategies can be targeted toward systems or individuals. At the system or departmental level, institutions can support radiologists through a formalized peer-review processes, continuing medical education, and implementation of structural changes to the work environment (eg, adjusting work hours to limit fatigue, reducing number of interruptions) [46,912]. At the individual level, radiologists can reduce their errors by participating in peer review and being mindful of the types of errors that occur in their specific work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to radiology, a 20-year retrospective analysis estimates the error rate leading to clinically significant outcomes to be between 2% and 20% [2] depending on modality or system of study. The literature provides us with a systems-based analysis of the causes, classifications, consequences, and prevention of error in radiology [3–9], as well as an entire “Pearls and Pitfalls” (2010–2016) series devoted to anatomic variants and mimics within subspecialty radiology [3]. We aim to provide readers with a concise summary of the common types of errors using cases from our institution that are specific to abdominal cross-sectional imaging.…”
mentioning
confidence: 99%